Undiagnosed Hemoglobinopathies: A potential threat to the premarital screening program: Undiagnosed Hemoglobinopathies - Hamali, Hassan Abdu; Saboor, Muhammad (Pakistan Journal of Medical Sciences, 2019)
Objectives: To evaluate the prevalence of undiagnosed hemoglobinopathies among individuals visiting the premarital screening Centre.Methods: This study was conducted at Premarital Screening Centre, King Fahad Central Hospital and Research Centre, Jazan, between January 2018 and October 2018. A total of 3,970 (male n =1,859 and female n = 2,111) individuals were included in the study. Data of complete blood count, hemoglobin electrophoresis and sickling tests of all individuals recruited in the study were obtained and statistically analyzed.Results: One thousand three hundred and twelve individuals had abnormal complete blood counts or hemoglobin electrophoresis results, that include sickle cell trait (13.5%), sickle cell disease (0.7%), β thalassemia with sickle cell trait (2.46%), β thalassemia trait (1.51%), β thalassemia major (0.075%), suspected α thalassemia or other hemoglobinopathies (4.43%), hemoglobin H (0.3%), hemoglobin E (0.075%), undiagnosed cases (0.91%) and iron deficient (7.23%).Conclusion: A high percentage of individuals are suspected for α thalassemia or other hemoglobinopathies that needs to be diagnosed. Further investigations shall be included in the premarital screening program to diagnose these inconclusive cases. Coexistence iron deficiency with thalassemia shall also be ruled out during premarital screening program.doi: https://doi.org/10.12669/pjms.35.6.976How to cite this:Hamali HA, Saboor M. Undiagnosed Hemoglobinopathies: A potential threat to the premarital screening program. Pak J Med Sci. 2019;35(6):1611-1615.  doi: https://doi.org/10.12669/pjms.35.6.976This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.